A Randomized Controlled Trial To Assess The Role Of Manual Lymphatic Drainage In Population With Breathing Dissociation Through Musculoskeletal And Fascial Modulation - Naqvi, Sumbul; Khan, Jafar; Kumar, Sunil; A Chobisa, Chitrakshi; Pal, Renuka; Jain, Preksha; Khera, Neha; Joshi, Jayesh; Soni, Sourabh; Ramawat, Prashant; Ansari, Adil Raza (Journal of Neonatal Surgery, 2025)
Background: Breathing dissociation is a dysfunctional respiratory pattern often associated with altered musculoskeletal dynamics, poor diaphragmatic engagement, and upper chest-dominant breathing. This condition contributes to sympathetic overactivation, impaired oxygenation, and compromised lymphatic flow. Musculoskeletal restrictions—particularly in the thoracic cage, fascia, and diaphragm—can inhibit lymphatic return and perpetuate inflammatory stasis. Manual Lymphatic Drainage (MLD), a structured hands-on technique, addresses these mechanical restrictions, facilitates fascial release, and promotes lymphatic propulsion—thereby offering a biomechanical approach to correcting dysfunctional breathing. Objective: This randomized controlled trial aimed to assess the therapeutic impact of MLD on individuals with breathing dissociation by targeting musculoskeletal and fascial elements that influence lymphatic flow and respiratory coordination. Methods: Thirty participants aged 25–60 years with clinically confirmed breathing dissociation were enrolled and treated with a standardized MLD protocol over four weeks, followed by two weeks of weekly follow-up. Techniques included superficial and deep lymphatic drainage focused on the thoracic cage, intercostals, diaphragm, and cervical lymphatics. Outcome measures included the Borg CR10 scale and Pulmonary Function Tests (FVC, FEV1, PEFR), analyzed pre- and post-intervention using paired t-tests. Results: Post-intervention analysis revealed statistically significant improvements in all measured parameters. Borg CR10 scores reduced from a mean of 6.40 to 2.47 (p < 0.001), FVC increased from 2.64L to 3.36L (p < 0.001), FEV1 improved from 2.02L to 2.64L (p < 0.001), and PEFR rose from 263.33 to 340.67 L/min (p < 0.001). These results highlight enhanced respiratory efficiency and musculoskeletal restoration through targeted lymphatic facilitation. Conclusion: Manual Lymphatic Drainage effectively improves respiratory function and alleviates symptoms of breathing dissociation by addressing underlying musculoskeletal and fascial impairments. The findings support MLD as a valuable intervention in respiratory rehabilitation, with potential to restore diaphragmatic mechanics, thoracic mobility, and autonomic balance in affected individuals.